The effectiveness of the Team Assisted Individualization model assisted by mathematics domino on mathematics learning outcomes of high school students - Ainun, Nurul; Agustyaningrum, Nina; Amelia, Fitrah (Universitas Riau Kepulauan, 2023)
This study was inspired by the class X SMA Hidayatullah Batam's poor mathematics learning outcomes, one of which was brought on by teaching strategies that discouraged student participation in the learning process. The purpose of this study was to compare the Team Assisted Individualization learning model assisted by mathematics domino (domat) visualizer with conventinal learning models in terms of the mathematics learning results for class X students at SMA Hidayatullah Batam. This kind of research utilized a posttest-only control group design and was quasi-experimental in nature. Up to 53 pupils from class X at SMA Hidayatullah made up the research population. The experimental class, X MIPA PA (15 students), and the control class, X MIPA PI (15 students), were sampled via purposive sampling. The research instrument was in the form of essay questions where all items were valid and reliable (reliability coefficient 0.927 in the high category). Using one sample t-test and independent sample t-tests the data were analyzed. The results showed: (1) The implementation of the domat-assisted TAI learning model was effective in terms of mathematics learning outcomes with a t-value (4.231) t-table (2.144); (2) the conventional model is ineffective with a t-value (-0.728) ≤ t-table (2.144); and (3) there were differences between the domat-assisted TAI learning model and the conventional model in terms of the outcomes of mathematics learning with a t-value (3.082) t-table (2.048). On the basis of the study's findings, the domat-assisted TAI learning approach is advised as an alternative to learning mathematics. It can help students take an active part in the learning process and improve their learning outcomes.